Resin composition, dental material, and mouth guard

JP2025022750APending Publication Date: 2025-02-14MITSUI CHEMICALS INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024090852
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-01
Filing Date
2024-06-04
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0011】 本開示によれば、変色が抑制された樹脂組成物、歯科材料、及びマウスガードを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025022750000001
    Figure 2025022750000001
  • Figure 2025022750000002
    Figure 2025022750000002
  • Figure 2025022750000003
    Figure 2025022750000003
Patent Text Reader

Abstract

To provide a resin composition resistant to discoloration, a dental material, and a mouth guard.SOLUTION: A resin composition comprises an α-olefinic polymer and an inorganic compound with at least one metal component selected from the group consisting of silver and zinc carried thereon, and exhibits a Shore A hardness of 5-90 at 37°C.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a resin composition, a dental material, and a mouth guard. [Background technology]

[0002] In sports involving strenuous movements such as boxing, rugby, and American football, protective equipment commonly known as mouthguards (also called mouthpieces) are widely used to protect the dentition and soft tissues in the mouth and to cushion the brain from impact.

[0003] Traditionally, mouth guards made of ethylene-vinyl acetate copolymer (EVA) have been known, but these have problems such as low shock absorption and being easily damaged by biting forces, so various types of mouth guards have been developed.

[0004] For example, Patent Document 1 discloses that a composition containing a 4-methyl-1-pentene-propylene copolymer consisting of structural units derived from 4-methyl-1-pentene and a thermoplastic resin can be used to manufacture mouthguard sheets and mouthguards (mainly sports mouthguards) that have excellent shock absorption properties, are thinner and lighter than conventional ones, and are comfortable to wear. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2012-40136 A Summary of the Invention [Problem to be solved by the invention]

[0006] Dental products such as mouthguards are sometimes required to have antibacterial properties. It is generally known that antibacterial agents such as silver are added to resin compositions to impart antibacterial properties, but the addition of the antibacterial agent may cause discoloration of dental materials molded from the resin compositions.

[0007] The present disclosure has been made in consideration of the above, and aims to provide a resin composition, a dental material, and a mouth guard that are inhibited from discoloring. [Means for solving the problem]

[0008] Means for solving the above problems include the following aspects. <1> A resin composition comprising an α-olefin polymer made of a hydrocarbon and an inorganic compound carrying at least one metal component selected from the group consisting of silver and zinc, the resin composition having a Shore A hardness of 5 to 90 at 37°C. <2> The inorganic compound comprises one or more compounds selected from the group consisting of aluminosilicates and phosphate glasses; <1> The resin composition according to claim 1. <3> The content of the inorganic compound is 0.01% by mass to 15% by mass with respect to the total amount of the resin composition. <1> or <2> The resin composition according to claim 1. <4> Further comprising a dispersant, <1> ~ <3> 10. The resin composition according to claim 9 . <5> The content of the dispersant is 0.01% by mass to 5% by mass with respect to the total amount of the resin composition. <4> The resin composition according to claim 1. <6> The dispersant comprises one or more compounds selected from the group consisting of fatty acids, fatty acid salts, fatty acid esters, modified polyolefins, and waxes. <4> or <5> The resin composition according to claim 1. <7> The dispersant contains a compound represented by the following general formula (1): <4> ~ <6> 10. The resin composition according to claim 9 .

[0009] [ka]

[0010] In general formula (1), R1 is a hydrocarbon group having 7 to 22 carbon atoms, R 2 represents a hydrogen atom, an alkali metal atom, an alkaline earth metal atom, or a hydrocarbon group which may have a substituent, and n is 1 to 3. R 2 is a hydrogen atom or an alkali metal atom, n is 1; R 2 is an alkaline earth metal atom, n is 2; R 2 When is a hydrocarbon group which may have a substituent, n is 1 to 3. <8> R 1 is an alkyl group having 12 to 20 carbon atoms; <7> The resin composition according to claim 1. <9> Contains modified polyolefin, a ratio of a structure derived from an unsaturated carboxylic acid and / or a derivative of an unsaturated carboxylic acid in the modified polyolefin to the entire resin composition is 0.000001% by mass to 0.25% by mass; <4> ~ <8> 10. The resin composition according to claim 9 . <10> For dental materials, <1> ~ <9> 10. The resin composition according to claim 9 . <11> For making mouthguards. <1> ~ <9> 10. The resin composition according to claim 9 . <12> <1> ~ <9> A dental material comprising the resin composition according to any one of the above items. <13> <1> ~ <9> A mouth guard comprising the resin composition according to any one of the above items. Effect of the Invention

[0011] According to the present disclosure, it is possible to provide a resin composition, a dental material, and a mouth guard that are inhibited from discoloring. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] In the present disclosure, a numerical range indicated using "~" includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples. In this disclosure, when referring to the amount of each component in a composition, if multiple substances corresponding to each component are present in the composition, it means the total amount of multiple substances present in the composition, unless otherwise specified. In the present disclosure, the specific inorganic compound may be read as a silver-supported zeolite, a zinc-supported zeolite, a silver- and zinc-supported zeolite, a silver-supported zirconium compound, a zinc-supported zirconium compound, or a silver- and zinc-supported zirconium compound.

[0013] [Resin composition] The resin composition of the present disclosure includes an α-olefin polymer made of a hydrocarbon and an inorganic compound carrying at least one metal component selected from the group consisting of silver and zinc (hereinafter also referred to as a "specific inorganic compound"). The resin composition has a Shore A hardness of 5 to 90 at 37°C. This suppresses discoloration of the resin composition. In particular, the use of a specific inorganic compound can suppress discoloration such as blackening, compared to the use of simple silver. In addition, the use of a specific inorganic compound makes it easier to maintain the same level of antibacterial effect compared to the use of simple silver.

[0014] The use of the resin composition of the present disclosure is not particularly limited. For example, the resin composition of the present disclosure may be used for dental materials, mouth guards, and the like.

[0015] The resin composition of the present disclosure has a Shore A hardness at 37° C. of 5 to 90. When the Shore A hardness value is within the above-mentioned range, the resin composition has excellent strength and processability, and when used as a mouth guard, it provides excellent chewing comfort, etc. The Shore A hardness is a value measured in accordance with JIS K6253 using a test piece having a thickness of 4 mm prepared from the resin composition.

[0016] In the resin composition of the present disclosure, the Shore A hardness at 37°C may be 10-80, 20-70, or 30-60.

[0017] From the viewpoints of the strength and processability of the resin composition, the biting comfort when made into a mouth guard, and the like, the Shore A hardness at 23°C of the resin composition of the present disclosure may be 30 to 100, 40 to 90, or 50 to 80.

[0018] (α-Olefin polymer) The resin composition of the present disclosure contains an α-olefin polymer made of hydrocarbon. The α-olefin polymer made of hydrocarbon means an α-olefin polymer made of only carbon atoms and hydrogen atoms. In other words, the α-olefin polymer made of hydrocarbon means an α-olefin polymer that is not modified with atoms other than carbon atoms and hydrogen atoms. Hereinafter, the "α-olefin polymer made of hydrocarbon" in the present disclosure is also simply referred to as "α-olefin polymer".

[0019] The α-olefin polymer is not particularly limited as long as it is a homopolymer or copolymer containing a structural unit derived from ethylene, a structural unit derived from propylene, a structural unit derived from an olefin having 4 or more carbon atoms, or the like. For example, polymerization components having 2 to 7 carbon atoms that serve as structural units of α-olefin polymers include ethylene, propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 4-methyl-1-pentene, 1-hexene, etc., and polymerization components having 8 or more carbon atoms that serve as structural units of α-olefin polymers include 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, etc.

[0020] The α-olefin polymer is preferably an α-olefin copolymer from the viewpoint of adjusting the Shore A hardness at 37° C. of the resin composition to 90 or less. The α-olefin copolymer refers to a copolymer in which two or more copolymerization components having an α-olefin skeleton are copolymerized.

[0021] Examples of copolymerization components having an α-olefin skeleton include α-olefins such as ethylene, propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene.

[0022] Examples of α-olefin copolymers include copolymers whose main component is a structural unit derived from ethylene, copolymers whose main component is a structural unit derived from propylene, etc. Specific examples of α-olefin copolymers include ethylene-propylene copolymers, copolymers of propylene and 4-methylpentene-1, and ethylene-octene copolymers. The α-olefin copolymer may be used alone or in combination of two or more kinds.

[0023] The α-olefin copolymer may be any of an alternating copolymer, a graft copolymer, a block copolymer and a random copolymer.

[0024] The content of the α-olefin copolymer in the α-olefin polymer is preferably 50% by mass to 100% by mass, more preferably 70% by mass to 100% by mass, and even more preferably 90% by mass to 100% by mass, based on the total amount of the α-olefin polymer.

[0025] From the viewpoint of adjusting the Shore A hardness at 37° C. in the resin composition to not more than 90, the α-olefin polymer preferably does not contain or contains a small amount of polyethylene homopolymer such as low-density polyethylene. For example, the content of polyethylene homopolymer is preferably 30% by mass or less, more preferably 10% by mass or less, further preferably 5% by mass or less, and particularly preferably 0% by mass, based on the total amount of the α-olefin polymer.

[0026] The content of the α-olefin copolymer is preferably 70% by mass to 100% by mass, more preferably 80% by mass to 100% by mass, even more preferably 90% by mass to 100% by mass, and particularly preferably 95% by mass to 100% by mass, based on the total amount of the resin composition.

[0027] The α-olefin copolymer may be a copolymer consisting of only two or more kinds of α-olefins. From the viewpoint of suitably suppressing discoloration of the resin composition, the α-olefin copolymer is preferably a copolymer consisting of only two or more kinds of α-olefins. The proportion of polymerizable monomers other than α-olefins constituting the α-olefin copolymer may be 20 mass% or less, 10 mass% or less, or may be 0 mass% to 5 mass% based on all structural units of the α-olefin copolymer.

[0028] The α-olefin copolymer may be a synthetic product or a commercially available product. When the α-olefin copolymer is a synthetic product, the α-olefin copolymer can be prepared by polymerizing or copolymerizing a monomer in the presence of a conventionally known catalyst such as a Ziegler-Natta catalyst or a metallocene catalyst by a conventionally known polymerization method such as a gas phase method, a bulk method, a slurry method, or a solution method. Examples of commercially available α-olefin copolymers include Tafmer (registered trademark, manufactured by Mitsui Chemicals), Vistamaxx series (manufactured by ExxonMobil Chemical Company), and Engage series (manufactured by Dow Chemical Company).

[0029] The weight average molecular weight (Mw) of the α-olefin polymer may be, for example, 50,000 to 1,000,000, preferably 80,000 to 800,000, and more preferably 100,000 to 500,000. In the present disclosure, the weight average molecular weight (Mw) is calculated in terms of polystyrene and measured by gel permeation chromatography (GPC), and means the mass average molecular weight (Mw) calculated in terms of polystyrene.

[0030] (Certain inorganic compounds) The resin composition of the present disclosure contains an inorganic compound (specific inorganic compound) carrying at least one metal component selected from the group consisting of silver and zinc. The specific inorganic compound is not particularly limited as long as it is an inorganic compound carrying at least one of silver and zinc. The specific inorganic compound may be an inorganic compound carrying only silver, an inorganic compound carrying only zinc, an inorganic compound carrying only silver and zinc, or an inorganic compound carrying at least one of silver and zinc and a component other than silver and zinc. The specific inorganic compounds may be used alone or in combination of two or more.

[0031] The shape of the inorganic compound on which at least one of silver and zinc is supported is not particularly limited, and may be, for example, in the form of particles. The inorganic compound on which at least one of silver and zinc is supported is preferably in the form of particles having a porous structure from the viewpoint of the supportability of the metal component.

[0032] The inorganic compound on which at least one of silver and zinc is supported is not particularly limited, and examples thereof include aluminosilicates (zeolites, etc.), silica gel, silicate glass, phosphate glass (calcium phosphate, zirconium phosphate, etc.), magnesium aluminometasilicate, clay minerals, ceramics, and the like. Examples of clay minerals include kaolin, montmorillonite, and talc. The inorganic compound on which at least one of silver and zinc is supported may be used alone or in combination of two or more kinds.

[0033] A specific inorganic compound can be obtained by supporting silver ions, zinc ions, etc. on an inorganic compound supporting at least one of silver and zinc through an ion exchange reaction.

[0034] From the viewpoints of antibacterial properties, ability to support metal components, etc., the specific inorganic compound preferably contains one or more compounds selected from the group consisting of silicon-containing compounds and zirconium-containing compounds.

[0035] The silicon-containing compound is not particularly limited as long as it contains silicon element, and examples thereof include aluminosilicates (such as zeolite), silica gel, silicate glass, magnesium aluminometasilicate, and the like. Among them, the silicon-containing compound preferably contains zeolite, and as the specific inorganic compound, silver-supported zeolite, zinc-supported zeolite, silver and zinc-supported zeolite, and the like are preferable. Examples of silicon-containing compounds contained in zeolites include silicon dioxide and aluminosilicates.

[0036] The zeolite (aluminosilicate) may be a natural zeolite or a synthetic zeolite. Specific examples of the zeolite include A-type zeolite, X-type zeolite, Y-type zeolite, T-type zeolite, high silica zeolite, sodalite, mordenite, analcime, clinoptilolite, chabazite, erionite, and the like.

[0037] The zeolite may be, for example, a compound represented by the following formula (1): XM 2 / n O·Al2O3·YSiO2·ZH2O···(1) In formula (1), M is an element such as silver or sodium, X, Y and Z are the molar ratios of each component, and n is the atomic valence of M.

[0038] The zirconium-containing compound is not particularly limited as long as it contains zirconium element, and examples thereof include zirconium phosphate and zirconium dioxide.

[0039] The inorganic compound on which at least one of silver and zinc is supported may contain a phosphorus compound such as zirconium phosphate, phosphorus oxide, calcium phosphate, etc. In particular, the phosphorus compound is preferably a phosphate glass. Furthermore, it is preferable that the inorganic compound contains a zirconium-containing compound (particularly, zirconium phosphate).

[0040] When the specific inorganic compound includes a zirconium-containing compound, the specific inorganic compound may include a silver-loaded zirconium compound, a zinc-loaded zirconium compound, or a silver and zinc-loaded zirconium compound.

[0041] From the viewpoints of antibacterial properties, ability to support metal components, etc., the specific inorganic compound preferably contains one or more compounds selected from the group consisting of aluminosilicates and phosphate glasses.

[0042] The specific inorganic compound has excellent antibacterial properties and suppresses discoloration caused by sulfur components. In the resin composition of the present disclosure, if the content of the specific inorganic compound is high, for example, physical properties such as bending strength may decrease, and if the content of the specific inorganic compound is low, the effect of suppressing discoloration can be more effectively exhibited. From these viewpoints, it is preferable that the content of the specific inorganic compound is low, while it is preferable that the content of the specific inorganic compound is high in order to exhibit antibacterial properties. In other words, if the specific inorganic compound can exhibit antibacterial properties with a smaller amount, it is possible to suppress the decrease in physical properties such as bending strength while increasing the discoloration suppression effect. From this viewpoint, the specific inorganic compound in the present disclosure is preferably an aluminosilicate (such as zeolite).

[0043] The amount of silver in the specific inorganic compound is preferably 0.1% by mass to 5.0% by mass, and more preferably 0.3% by mass to 3.0% by mass, and the amount of zinc in the specific inorganic compound is preferably 5.0% by mass to 30% by mass, and more preferably 10% by mass to 20% by mass.

[0044] When the specific inorganic compound is in particulate form, the volume average particle diameter (D50) of the particles may be, for example, 0.1 μm to 20 μm, 0.5 μm to 15 μm, 1.0 μm to 12 μm, or 3.0 μm to 12 μm. The volume average particle size (D50) of the particles can be measured using a laser diffraction / scattering type particle size distribution measuring device.

[0045] From the viewpoint of antibacterial properties and preventing excessive use of the specific inorganic compound, the content of the specific inorganic compound is preferably 0.01 mass% to 15 mass%, more preferably 0.1 mass% to 15 mass%, even more preferably 0.5 mass% to 10 mass%, and particularly preferably 1 mass% to 8 mass%, relative to the total amount of the resin composition.

[0046] From the viewpoint of antibacterial properties and preventing excessive use of the specific inorganic compound, the content of the specific inorganic compound is preferably 0.01 parts by mass to 20 parts by mass, more preferably 0.01 parts by mass to 10 parts by mass, even more preferably 0.1 parts by mass to 8 parts by mass, and particularly preferably 0.5 parts by mass to 5 parts by mass, relative to 100 parts by mass of the α-olefin polymer.

[0047] (Dispersant) The resin composition of the present disclosure preferably further contains a dispersant, which tends to suppress discoloration of the resin composition over time in the presence of moisture.

[0048] The dispersant preferably comprises one or more compounds selected from the group consisting of fatty acids, fatty acid salts, fatty acid esters, modified polyolefins, and waxes.

[0049] The fatty acid is preferably a higher fatty acid having 11 to 23 carbon atoms, more preferably a higher fatty acid having 13 to 21 carbon atoms. The fatty acid may be a saturated fatty acid or an unsaturated fatty acid, and is preferably a saturated fatty acid from the viewpoint of suppressing discoloration of the resin composition. In particular, when the polymerization component that becomes the constituent unit of the α-olefin polymer contains a polymerization component having 2 to 7 carbon atoms that becomes the constituent unit of the α-olefin polymer, from the viewpoint of suppressing discoloration of the resin composition, the dispersant is preferably a saturated fatty acid, or a higher fatty acid having 11 to 23 carbon atoms, and more preferably a higher fatty acid having 13 to 21 carbon atoms. On the other hand, when the polymerization components that become the constituent units of the α-olefin polymer contain a polymerization component having 8 or more carbon atoms (preferably a polymerization component having 8 to 12 carbon atoms) that becomes the constituent units of the α-olefin polymer, the dispersant is preferably a higher fatty acid having 8 to 25 carbon atoms (which may be either a saturated fatty acid or an unsaturated fatty acid).

[0050] Examples of fatty acid salts include alkali metal salts of fatty acids such as sodium salts of fatty acids, alkaline earth metal salts of fatty acids such as magnesium salts of fatty acids and calcium salts of fatty acids, and zinc salts of fatty acids. Examples of the fatty acid constituting the fatty acid salt include the fatty acids mentioned above.

[0051] Examples of fatty acid esters include polyhydric alcohol fatty acid esters such as glycerin fatty acid esters and sorbitan fatty acid esters, and polyoxyalkylene fatty acid esters such as polyoxyethylene fatty acid esters and polyoxypropylene fatty acid esters. Examples of the fatty acid constituting the fatty acid ester include the fatty acids mentioned above.

[0052] The modified polyolefin may be a polyolefin modified with an unsaturated carboxylic acid, a derivative of an unsaturated carboxylic acid, a diamine, a carbodiimide, or the like. The modified polyolefin is preferably a polyolefin modified with one or more selected from the group consisting of an unsaturated carboxylic acid and a derivative of an unsaturated carboxylic acid. The modified polyolefin in the present disclosure does not include the above-mentioned α-olefin polymer.

[0053] The polyolefin constituting the modified polyolefin is not particularly limited as long as it is a homopolymer or copolymer containing a structural unit derived from ethylene, a structural unit derived from propylene, a structural unit derived from an olefin having 4 or more carbon atoms, etc. The polyolefin constituting the modified polyolefin preferably contains a structural unit derived from propylene, and is preferably an α-olefin copolymer of propylene and other monomers. Examples of the olefin copolymerized with propylene include ethylene and α-olefins having 4 to 20 carbon atoms, and preferably ethylene and α-olefins having 4 to 10 carbon atoms. In the α-olefin copolymer of propylene and other monomers, the content of the structural unit derived from propylene is preferably 50 mol% or more and less than 100 mol%.

[0054] The method for producing the modified polyolefin is not particularly limited, and a polyolefin to be modified may first be produced by a method using a well-known catalyst such as a Ziegler-Natta catalyst or a metallocene catalyst, and then the produced polyolefin may be subjected to a known graft polymerization method such as a solution method or a melt kneading method using a modifying raw material such as an unsaturated carboxylic acid or a derivative of an unsaturated carboxylic acid to produce the modified polyolefin.

[0055] The α-olefin copolymer to be modified in the modified polyolefin may be any of an alternating copolymer, a graft copolymer, a block copolymer and a random copolymer.

[0056] Examples of the unsaturated carboxylic acid or derivative of unsaturated carboxylic acid that modifies the modified polyolefin include an unsaturated compound having one or more carboxy groups, an ester of a compound having a carboxy group and an alkyl alcohol, an unsaturated compound having a structure represented by R-CO-O-CO-R' (R and R' are each independently a hydrocarbon group), and an unsaturated compound having one or more structures represented by -CO-O-CO- in one molecule. Examples of the unsaturated group contained in the unsaturated compound include a vinyl group, a vinylene group, and an unsaturated cyclic hydrocarbon group. The unsaturated carboxylic acid or derivative of unsaturated carboxylic acid may be used alone or in combination of two or more. The derivative of unsaturated carboxylic acid may be unsaturated or saturated. Examples of the unsaturated carboxylic acid or derivative of unsaturated carboxylic acid include unsaturated dicarboxylic acids such as maleic acid and nadic acid, and anhydrides thereof. The unsaturated carboxylic acid or derivative of unsaturated carboxylic acid is preferably an unsaturated dicarboxylic acid or anhydride of unsaturated carboxylic acid, more preferably maleic acid, nadic acid, or anhydride thereof, and even more preferably maleic anhydride.

[0057] The proportion of the structure derived from the unsaturated carboxylic acid and / or the derivative of the unsaturated carboxylic acid in the modified polyolefin is preferably 0.01% by mass to 5% by mass, more preferably 0.05% by mass to 3.5% by mass, based on the entire modified polyolefin. In particular, when the polyolefin is modified with maleic anhydride, the proportion of the structure derived from maleic anhydride is preferably within the above range. In the present disclosure, the term "unsaturated carboxylic acid and / or a derivative of an unsaturated carboxylic acid" refers to either an unsaturated carboxylic acid or a derivative of an unsaturated carboxylic acid, or the sum of an unsaturated carboxylic acid and a derivative of an unsaturated carboxylic acid.

[0058] The polyolefin to be modified preferably contains 50 mol % to 100 mol % of structural units derived from propylene.

[0059] The method for modifying a polyolefin with an unsaturated carboxylic acid and / or a derivative of an unsaturated carboxylic acid to prepare a modified polyolefin is not particularly limited, and a solution method, a melt kneading method, or the like may be used.

[0060] The weight average molecular weight (Mw) of the modified polyolefin is preferably 50,000 to 1,000,000, and more preferably 100,000 to 700,000.

[0061] When the resin composition of the present disclosure contains a modified polyolefin, the proportion of the structure derived from the unsaturated carboxylic acid and / or a derivative of the unsaturated carboxylic acid in the modified polyolefin relative to the entire resin composition of the present disclosure is preferably 0.000001% by mass to 0.25% by mass.

[0062] Examples of waxes include polyolefin waxes and paraffin waxes. Among these, polyolefin waxes are particularly preferred. Note that the polyolefin wax in the present disclosure does not include the above-mentioned α-olefin polymers and modified polyolefins, but is a polyolefin other than the α-olefin polymers and modified polyolefins.

[0063] Examples of polyolefin waxes include ethylene homopolymers, copolymers of ethylene and an α-olefin having 3 or more carbon atoms, propylene homopolymers, and copolymers of propylene and ethylene or an α-olefin having 4 or more carbon atoms.

[0064] The weight average molecular weight of the polyolefin wax is preferably 1,000 to 30,000, more preferably 5,000 to 20,000, and even more preferably 8,000 to 15,000.

[0065] The dispersant preferably contains a compound represented by the following general formula (1).

[0066] [ka]

[0067] In general formula (1), R 1 is a hydrocarbon group having 7 to 22 carbon atoms, R 2 represents a hydrogen atom, an alkali metal atom, an alkaline earth metal atom, or a hydrocarbon group which may have a substituent, and n is 1 to 3. R 2 is a hydrogen atom or an alkali metal atom, n is 1; R 2 is an alkaline earth metal atom, n is 2; R 2 When is a hydrocarbon group which may have a substituent, n is 1 to 3. When n is 2 or 3, multiple R 2 may be the same or different.

[0068] R 1 is a hydrocarbon group having 7 to 22 carbon atoms, and from the viewpoint of suppressing discoloration of the resin composition, is preferably an alkyl group having 10 to 20 carbon atoms, and more preferably an alkyl group having 12 to 20 carbon atoms. In particular, when the polymerization component of the structural unit of the α-olefin polymer contains a polymerization component having 2 to 7 carbon atoms that becomes a structural unit of the α-olefin polymer, from the viewpoint of suppressing discoloration of the resin composition, an alkyl group having 12 to 20 carbon atoms is more preferable. For example, R 1 may be an alkyl group having 15 to 17 carbon atoms. On the other hand, when the polymerization component of the structural unit of the α-olefin polymer contains a polymerization component having 8 or more carbon atoms that is a structural unit of the α-olefin polymer, R 1 is preferably a hydrocarbon group having 7 to 24 carbon atoms, and when a polymerization component having 8 to 12 carbon atoms that serves as a structural unit of an α-olefin polymer is included, R 1 is preferably an alkyl group having 10 to 24 carbon atoms.

[0069] R 2 Examples of the alkali metal atom in the formula include a lithium atom, a sodium atom, and a potassium atom. R 2Examples of the alkaline earth metal atom in include a magnesium atom and a calcium atom. Examples of the hydrocarbon group which may have a substituent include a hydrocarbon group having a substituent such as a hydroxy group, a carboxy group, an amino group, or a halogen atom. The hydrocarbon group which may have a substituent may be a residue in which at least one hydroxy group has been removed from a hydrocarbon group having a hydroxy group, for example, a residue in which one to three hydroxy groups have been removed from glycerin.

[0070] Examples of the compound represented by the general formula (1) include Fatty acids such as lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, and behenic acid; Alkali metal salts of these fatty acids, such as lithium salts, sodium salts, and potassium salts; alkaline earth metal salts of these fatty acids, such as magnesium salts and calcium salts; Glycerol monoesters of these fatty acids, Glycerol diesters of these fatty acids, Glycerol triesters of these fatty acids etc.

[0071] The content of the dispersant is preferably 0.01% by mass to 5% by mass, more preferably 0.03% by mass to 3% by mass, and further preferably 0.05% by mass to 1% by mass, based on the total amount of the resin composition.

[0072] (Other Ingredients) The resin composition of the present disclosure may contain other components in addition to the α-olefin polymer, the specific inorganic compound, and the dispersant. Examples of other components include polymer components other than the α-olefin polymer, fillers such as organic fillers and inorganic fillers (excluding the specific inorganic compounds), antibacterial components other than the specific inorganic compounds, softeners, various weather stabilizers, heat stabilizers, antioxidants, UV absorbers, antistatic agents, antislip agents, antiblocking agents, antifogging agents, nucleating agents, lubricants, pigments, dyes, antioxidants, hydrochloric acid absorbers, inorganic or organic fillers, organic or inorganic foaming agents, crosslinking agents, co-crosslinking agents, crosslinking assistants, adhesives, flame retardants, and additives such as release agents.

[0073] [Dental Materials] The dental material of the present disclosure includes the resin composition of the present disclosure. The dental material is not particularly limited as long as it is used for dental purposes, and examples of the dental material include a molded product of the resin composition and a mouth guard sheet. For example, a mouthguard sheet can be produced by forming the resin composition of the present disclosure into a sheet by any molding method such as extrusion molding, calendar molding, press molding, injection molding, vacuum molding, pressure molding, or vacuum pressure molding.

[0074] [Mouthguard] The mouthguard of the present disclosure comprises the resin composition of the present disclosure. The mouth guard of the present disclosure can be produced, for example, by using the mouth guard sheet of the present disclosure which is made of a molded article of the resin composition of the present disclosure. The mouthguard of the present disclosure can be manufactured in the same manner as conventional mouthguards, for example, by the method described in International Publication No. 2002 / 98521 and Japanese Patent Application Laid-Open No. 2010-131181, except that the material is the resin composition or mouthguard sheet of the present disclosure. More specifically, the mouthguard can be manufactured by a method of heating the mouthguard sheet until it softens and manufacturing the mouthguard by fitting it to a dentition model or jaw model, or by a method of manufacturing the mouthguard by creating a concave mold using a dentition model or jaw model and injecting the resin composition into it. EXAMPLES

[0075] Examples of the present disclosure will be described below, but the present disclosure is not limited to the following examples.

[0076] [Examples 1 to 26 and Comparative Examples 1 to 4] In Examples 1 to 26 and Comparative Examples 1 to 4, resin compositions prepared by kneading each compound in the compounding ratio (parts by mass) shown in Table 1 were used to prepare test pieces as described below. The components used in each of the examples and comparative examples are as follows. -α-Olefin polymer- Polymer 1: Ethylene-propylene copolymer (ExxonMobil VISTAMAXX 6202), weight average molecular weight (Mw): 207,000 Polymer 2: Copolymer of propylene and 4-methylpentene-1, weight average molecular weight (Mw): 390,000 Polymer 3: Ethylene-octene copolymer (Engage 8200, manufactured by Dow Chemical Company), weight average molecular weight (Mw): 158,000 -Inorganic compounds or materials- Inorganic Compound 1: Silver-loaded Phosphate Glass Inorganic compound 2: Silver-loaded zeolite Inorganic material: silver -Dispersant- Dispersant 1: Stearic acid Dispersant 2: Magnesium stearate Dispersant 3: Sodium laurate Dispersant 4: Glycerol monostearate Dispersant 5: Glycerol distearate Dispersant 6: Polyolefin wax (ethylene homopolymer), weight average molecular weight (Mw): 13,400 Dispersant 7: Polyolefin wax (ethylene-propylene copolymer), Mitsui Chemicals 420P), weight average molecular weight (Mw): 14700 Dispersant 8: Modified homopolypropylene (amount of structure derived from maleic anhydride (graft modification amount): 0.5% by mass)

[0077] (Synthesis Example 1) <Synthesis of polyolefin wax as dispersant 6> A 1.5 L stainless steel pyrolysis apparatus equipped with a stirrer, nitrogen inlet tube, and condenser was charged with high-pressure low-density polyethylene (MFR [190°C, 2.16 kg] = 20 g / 10 min, density 917 kg / m 3 ) was added and thoroughly substituted with nitrogen. Next, the pyrolysis apparatus was heated to 430°C while nitrogen was still flowing in, and the polyethylene was melted, and then stirring was started. After the polyethylene reached the specified temperature, it was heated for 75 minutes to carry out pyrolysis. Thereafter, the pyrolysis apparatus was cooled to room temperature to obtain a polyolefin wax (pyrolyzed product) of dispersant 6.

[0078] [Weight average molecular weight (Mw)] The weight average molecular weight (Mw) of the α-olefin polymer was measured using a liquid chromatograph: Waters ALC / GPC 150-C plus type (integrated differential refractometer detector) with two Tosoh Corporation GMH6-HT columns and two GMH6-HTL columns connected in series, o-dichlorobenzene as the mobile phase medium, at a flow rate of 1.0 ml / min and 140°C. The obtained chromatogram was analyzed by a known method using a calibration curve prepared using a standard polystyrene sample to calculate Mw. The measurement time per sample was 60 minutes.

[0079] [Preparation of test specimens] A strand was prepared by kneading and extruding each compound corresponding to the composition of the test piece used in the coloring evaluation using a small kneader (MC15, manufactured by DSM). The inorganic compound and dispersant were mixed at a ratio of 3% by mass and 0.1% by mass, respectively, relative to the mass of the test piece. After kneading for 3 minutes at 200°C using a twin screw at a rotation speed of 100 ppm, the mixture was extruded as a strand. The strand was cut using a water-cooled pelletizer (KM-100H L120, manufactured by Katsumik Co., Ltd.) to prepare pellets of the test piece composition. The pellets of the test specimen composition were laid out in a silicon mold, melted by a microwave molding machine (M150, manufactured by D-MEC), and cooled while pressing by a press machine (FP7, manufactured by Morita Tokyo Mfg. Co., Ltd.) to produce a test specimen. The microwave molding conditions were to increase the temperature to a maximum of 160°C at a rate of 2°C / min, and to hold the temperature at 160°C for 10 minutes. Each composition (strand, pellet, test piece) obtained in the test piece preparation process was vacuum dried and stored to suppress moisture absorption.

[0080] [Shore A hardness measurement] In measuring the Shore A hardness (based on JIS K6253), a test piece having a thickness of 4 mm was used as the measurement sample, and the scale was read 15 seconds after the indenter contacted the sample. Measurements were performed both at 37°C and at room temperature (23°C). As a result, the Shore A hardness at 37° C. of each test piece of the resin compositions of Examples 1 to 26 was all within the range of 30 to 65. Moreover, the Shore A hardness at 23° C. of each of the test pieces of the resin compositions of Examples 1 to 26 was all within the range of 60 to 80.

[0081] [Coloring evaluation immediately after resin molding] The color of the test pieces (7cm x 7cm x 4mm) immediately after preparation was evaluated using a spectrophotometer (SD3000, manufactured by Mitsuwa Frontech Co., Ltd.). Measurements were taken at three points on each test piece, and the average value was used to calculate the color difference ΔE. The calculation method for the color difference ΔE is as follows. The unprocessed test pieces used in this test correspond to test pieces having only the resin composition. ΔE = [(ΔL) 2 +(Δa) 2 +(Δb) 2 〕 1 / 2 ΔE: Color difference between unprocessed test piece and evaluation test piece ΔL: Difference between the L value (brightness) of the unprocessed test piece and the L value of the evaluation test piece Δa: Difference between the a value of the unprocessed test piece (color change from red to green) and the a value of the evaluation test piece Δb: Difference between the b value of the unprocessed test piece (color change from yellowish to blueish) and the b value of the evaluation test piece Using the color difference ΔE value calculated by the above method, coloring was evaluated according to the following criteria. A: ΔE is 1.0 or more and less than 8.0 B: ΔE is 8.0 or more and less than 15.0 C: ΔE is 15.0 or more and less than 25.0 The results are shown in Table 1.

[0082] [Evaluation of color change over time when immersed in water] Test pieces (7cm x 7cm x 4mm) were immersed in ultrapure water and left to stand at room temperature. The test pieces were removed on the 0th and 30th days and the color change over time was quantified using a spectrophotometer (SD3000, Mitsuwa Frontech Co., Ltd.). Measurements were taken at three points on each test piece, and the average value was used to calculate the color difference ΔE. The method for calculating the color difference ΔE was the same as the method described above in [Evaluation of color change immediately after resin molding]. The coloring evaluation was also performed according to the same criteria as in the method described in [Evaluation of coloring immediately after resin molding]. The results are shown in Table 2.

[0083] [Table 1]

[0084] [Table 2]

[0085] [Table 3]

[0086] Examples 1 to 5, in which a specific inorganic compound was used, had better coloring evaluation than Comparative Examples 1 to 4, in which silver was used. Furthermore, in Examples 6 to 26, in which a specific inorganic compound was used, the color evaluation was likely to be maintained even after 30 days had passed. In particular, in Examples 6 to 24, in which a dispersant was used, and Example 26, in which Polymer 3 was used, no change in the color evaluation was observed even after 30 days had passed.

Claims

1. A resin composition comprising an α-olefin polymer made of a hydrocarbon and an inorganic compound carrying at least one metal component selected from the group consisting of silver and zinc, the resin composition having a Shore A hardness of 5 to 90 at 37°C.

2. The resin composition according to claim 1 , wherein the inorganic compound comprises one or more compounds selected from the group consisting of aluminosilicates and phosphate glasses.

3. The resin composition according to claim 1, wherein the content of the inorganic compound is 0.01% by mass to 15% by mass with respect to the total amount of the resin composition.

4. The resin composition according to claim 1 , further comprising a dispersant.

5. The resin composition according to claim 4, wherein the content of the dispersant is 0.01% by mass to 5% by mass based on the total amount of the resin composition.

6. The resin composition according to claim 4 , wherein the dispersant comprises one or more compounds selected from the group consisting of fatty acids, fatty acid salts, fatty acid esters, modified polyolefins, and waxes.

7. The resin composition according to claim 4 , wherein the dispersant comprises a compound represented by the following general formula (1): 【Chemistry 1】 In general formula (1), R 1 is a hydrocarbon group having 7 to 22 carbon atoms, R 2 represents a hydrogen atom, an alkali metal atom, an alkaline earth metal atom or a hydrocarbon group which may have a substituent, n is 1 to 3, R 2 is a hydrogen atom or an alkali metal atom, n is 1; R 2 is an alkaline earth metal atom, n is 2; R 2 When is a hydrocarbon group which may have a substituent, n is 1 to 3.

8. The R 1 The resin composition according to claim 7, wherein is an alkyl group having 12 to 20 carbon atoms.

9. The modified polyolefin is contained, The ratio of the structure derived from the unsaturated carboxylic acid and / or the derivative of the unsaturated carboxylic acid in the modified polyolefin to the entire resin composition is 0.000001 mass % to 0.25 mass %. The resin composition according to claim 4.

10. The resin composition according to any one of claims 1 to 9, which is used as a dental material.

11. The resin composition according to any one of claims 1 to 9, which is for producing a mouth guard.

12. A dental material comprising the resin composition according to any one of claims 1 to 9.

13. A mouth guard comprising the resin composition according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Composition for mouth guard, sheet for mouth guard, and mouth guard

    JP2012040136A